Rugby Union: faster, higher, stronger: keeping an evolving sport safe - Murray, A. D.; Murray, I. R.; Robson, J. (British Journal of Sports Medicine, 2014)
Since the International Rugby Board (IRB) declared Rugby Union an open game thus effectively ushering in professionalism, players have become faster and stronger. Force equals mass multiplied by acceleration: logically increased force at collision will lead to more injuries. Surveillance studies and injury databases have provided comprehensive datasets which confirm changing patterns of injury in rugby. We examine what is being done, and how safety can be improved in rugby. Rugby Union is experiencing unprecedented global growth. In total, 3.5 million men, women and children play worldwide, with 117 Unions in membership of the IRB. Modern rugby is ever more physically demanding due to increases in ball in play time, and speed of play. A fourfold increase in tackles and rucks per game has been noted.4-6 Teams with the tallest and heaviest players outperformed others in the Rugby World Cup. The IRB have appointed a Chief Medical Officer, a safety consultant and working groups to ensure that safety is maintained. Injury trends: Epidemiological data provide insight into changes in the nature and frequency of injuries. Some injuries are unavoidable and "uncontrollable", whereas others result from dangerous play. An international consensus statement on definitions and procedures used for injury surveillance has allowed meaningful comparisons of results across studies